1993
DOI: 10.1080/1120009x.1993.11755468
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Ciclopirox Olamine after Vaginal Application to Rabbits and Patients

Abstract: The authors reported the plasma levels and pharmacokinetic parameters of ciclopirox olamine in rabbits after i.v. and intravaginal administrations and in female patients after vaginal administration. Plasma levels of total and free ciclopirox were determined by a HPLC method. In rabbit ciclopirox showed a half-life of 2.22 h and an intravaginal bioavailability of about 2%. In female patients ciclopirox showed low intravaginal absorption; this value might explain the good local and systemic tolerability and als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Its use in treating vaginal candidiasis has also been studied, with limited success (9,17,21), and it has shown clinical promise against azole-resistant Candida species, including C. glabrata. It has demonstrated good topical and systemic tolerance in rats and rabbits when vaginal tissue was examined (5,15) and has been studied in settings with a lower pH (9,10). However, in this study, a 4-fold rise in MIC 90 from 0.5 to 2 g/ml with a decrease in pH was seen.…”
Section: Discussionmentioning
confidence: 99%
“…Its use in treating vaginal candidiasis has also been studied, with limited success (9,17,21), and it has shown clinical promise against azole-resistant Candida species, including C. glabrata. It has demonstrated good topical and systemic tolerance in rats and rabbits when vaginal tissue was examined (5,15) and has been studied in settings with a lower pH (9,10). However, in this study, a 4-fold rise in MIC 90 from 0.5 to 2 g/ml with a decrease in pH was seen.…”
Section: Discussionmentioning
confidence: 99%
“…CPX has shown an excellent safety profile and has appeared unable to promote resistance development in fungi in 31 years of use [ 24 , 28 , 29 , 30 ]. Oral, intravaginal, and topical administration routes for CPX have been investigated in humans, but its usage is limited as a topical agent due to poor oral or intravaginal bioavailability, gastrointestinal toxicity, and poor water solubility that limits its production as an injectable drug [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite only being marketed for topical use, in part because of the large quantity of antibiotics on the market at the time of its development, ciclopirox has been assessed for other purposes, including systemically [6–10]. Acute toxicity studies performed in mice and rats revealed LD 50s ranging from 1,700 to > 2,500 mg/kg (oral and subcutaneous), 71–79 mg/kg (intravenous), and 83–172 mg/kg (intraperitoneal).…”
Section: Introductionmentioning
confidence: 99%